2002
DOI: 10.1109/tns.2002.805406
|View full text |Cite
|
Sign up to set email alerts
|

Radiation effects in micro-electromechanical systems (MEMS): RF relays

Abstract: GaAs micro-electromechanical RF relays fabricated by surface micromachining techniques were characterized for their response to total ionizing dose. Microrelays with two different geometries were studied. For one geometry, changes in switch actuation voltage at moderate dose levels were observed. For an alternative geometry, no change in actuation voltage was observed. A mechanism for dielectric charge trapping and its effect on the electrostatic force is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(37 citation statements)
references
References 8 publications
0
36
1
Order By: Relevance
“…44 rf switches from Rockwell Scientific Company ͑Thousand Oaks, California͒ reported in Ref. 34 showed no change in static characteristics at doses of up to 150 krad for one design developed to reduce dielectric charging. For a more conventional design, the device's calibration started to change at doses of 10 krad, although the device continued to operate after doses of 300 krad, but with an 80% increase in required drive voltage.…”
Section: Electrostatic Microelectromechanical System Sensors and Actumentioning
confidence: 98%
See 1 more Smart Citation
“…44 rf switches from Rockwell Scientific Company ͑Thousand Oaks, California͒ reported in Ref. 34 showed no change in static characteristics at doses of up to 150 krad for one design developed to reduce dielectric charging. For a more conventional design, the device's calibration started to change at doses of 10 krad, although the device continued to operate after doses of 300 krad, but with an 80% increase in required drive voltage.…”
Section: Electrostatic Microelectromechanical System Sensors and Actumentioning
confidence: 98%
“…Tests on accelerometers and rf switches showed a marked change in calibration at doses above 30 krad. [32][33][34] Those failures were attributed to trapped charge in dielectric films. These doses are for unpackaged devices, so that the sensor element is directly irradiated.…”
Section: Survey Of Radiation Tests Performed Onmentioning
confidence: 99%
“…Knudson and Lee [103], [104] tested the performance of MEMS accelerometers under nuclear radiation and found that the change in output voltage was caused by charge buildup in dielectric layers beneath the moving mass. McClure [105] proposed a mechanism for creating a charge distribution in the dielectric of the MEMS device exposed to nuclear radiation. Newman et al [106] presented the contact surface of a wafer-packaged RF MEMS switch damaged by ESD.…”
Section: B Dielectric Breakdown Due To Electrostatic Dischargementioning
confidence: 99%
“…In both cases counteracting the effects of trapped charge is possible by following basic rules such as minimizing the volume of dielectrics in critical areas and by designing devices whose operation is insensitive to trapped charge [1]. This can significantly improve the reliability [2] but cannot eliminate material-specific limitations such as the degradation of the mechanical and electrical properties of the materials themselves. Appropriate material selection is therefore at the heart of engineering of reliable MEMS and is one of the main factors determining the performance and the failure modes of devices.…”
Section: Icro-electromechanical Systems (Mems)mentioning
confidence: 99%